Clinical Perspectives on the Use of Subcutaneous and Oral Formulations of Semaglutide - Gallwitz, Baptist; Giorgino, Francesco (Frontiers in Endocrinology, 2021)
Early and effective glycemic control can prevent or delay the complications associated with type 2 diabetes (T2D). The benefits of glucagon-like peptide-1 receptor agonists (GLP-1RAs) are becoming increasingly recognized and they now feature prominently in international T2D treatment recommendations and guidelines across the disease continuum. However, despite providing effective glycemic control, weight loss, and a low risk of hypoglycemia, GLP-1RAs are currently underutilized in clinical practice. The long-acting GLP-1RA, semaglutide, is available for once-weekly injection and in a new once-daily oral formulation. Semaglutide is an advantageous choice for the treatment of T2D since it has greater efficacy in reducing glycated hemoglobin and body weight compared with other GLP-1RAs, has demonstrated benefits in reducing major adverse cardiovascular events, and has a favorable profile in special populations (e.g., patients with hepatic impairment or renal impairment). The oral formulation represents a useful option to help improve acceptance and adherence compared with injectable formulations for patients with a preference for oral therapy, and may lead to earlier and broader use of GLP-1RAs in the T2D treatment trajectory. As with most GLP-1RAs, initial dose escalation of semaglutide is required for both formulations to mitigate gastrointestinal adverse events. There are also specific dose instructions to follow with oral semaglutide to ensure sufficient gastric absorption. The evidence base surrounding the clinical use of semaglutide is being further expanded with trials investigating effects on diabetic retinopathy, cardiovascular outcomes, and on the common T2D comorbidities of obesity, chronic kidney disease, and non-alcoholic steatohepatitis.